A Smart Sensor System for Detecting Hydrocarbon Volatile Organic Compounds in Sea Water. Issue 1 (14th July 2014) - Tonacci, Alessandro; Corda, Daniele; Tartarisco, Gennaro; Pioggia, Giovanni; Domenici, Claudio
<x xml:space="preserve">Abstract</x> Hydrocarbons are among the most dangerous pollutants for the marine environment. The creation of smart systems to detect hydrocarbon spills in the marine environment is often complex and involves many issues. This paper presents an innovative approach based on a sensor system capable of detecting volatile organic compounds (VOCs) produced by hydrocarbons. The system was composed of an array of photo ionization detectors, lodged in a flow chamber and arranged in radial symmetry, in order to receive the same amount of air flow. The air inlet was placed on the upper face of the chamber, while the air outlet was on the lower face. The sensor characterization at the laboratory bench was performed using different kinds of hydrocarbons, such as gasoline, diesel fuel, kerosene, and crude oil, and their response was acquired using a smart electronic system based on an Arduino™ electronic board. With this approach, it was possible to detect mild‐to‐high concentrations of VOCs with a portable, lightweight, smart system, placed in an autonomous underwater vehicle and in a moored buoy.